Increasing access to microfluidics for studying fungi and other branched biological structures - Millet, Larry J. (Fungal Biol Biotechnol, 2019)
BACKGROUND: Microfluidic systems are well-suited for studying mixed biological communities for improving industrial processes of fermentation, biofuel production, and pharmaceutical production. The results of which have the potential to resolve the underlying mechanisms of growth and transport in these complex branched living systems. Microfluidics provide controlled environments and improved optical access for real-time and high-resolution imaging studies that allow high-content and quantitative analyses. Studying growing branched structures and the dynamics of cellular interactions with both biotic and abiotic cues provides context for molecule production and genetic manipulations. To make progress in this arena, technical and logistical barriers must be overcome to more effectively deploy microfluidics in biological disciplines. A principle technical barrier is the process of assembling, sterilizing, and hydrating the microfluidic system; the lack of the necessary equipment for the preparatory process is a contributing factor to this barrier. To improve access to microfluidic systems, we present the development, characterization, and implementation of a microfluidics assembly and packaging process that builds on self-priming point-of-care principles to achieve “ready-to-use microfluidics.” RESULTS: We present results from domestic and international collaborations using novel microfluidic architectures prepared with a unique packaging protocol. We implement this approach by focusing primarily on filamentous fungi; we also demonstrate the utility of this approach for collaborations on plants and neurons. In this work we (1) determine the shelf-life of ready-to-use microfluidics, (2) demonstrate biofilm-like colonization on fungi, (3) describe bacterial motility on fungal hyphae (fungal highway), (4) report material-dependent bacterial-fungal colonization, (5) demonstrate germination of vacuum-sealed Arabidopsis seeds in microfluidics stored for up to 2 weeks, and (6) observe bidirectional cytoplasmic streaming in fungi. CONCLUSIONS: This pre-packaging approach provides a simple, one step process to initiate microfluidics in any setting for fungal studies, bacteria-fungal interactions, and other biological inquiries. This process improves access to microfluidics for controlling biological microenvironments, and further enabling visual and quantitative analysis of fungal cultures. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40694-019-0071-z) contains supplementary material, which is available to authorized users.